دراسة وبائية لنسبة السكريين غير المشخصين بين المرضى البالغين المقبولين في مشفى الأسد الجامعي - المرعي, منيف; درويش, علي; العلي, ناصر (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة للتحري عن انتشار الداء السكري غير المشخص لدى المرضى البالغين المقبولين في مشفى الأسد الجامعي باللاذقية, تناولت 345 مريض [189 ذكر (54%), 156 أنثى (46%)]. تراوحت أعمارهم بين 20-90 سنة, حيث أجري لهم تحليل سكر الدم على الريق مأخوذ من بلازما الدم الوريدي بالإضافة لاستجواب سريري, ودرسنا علاقة السكري غير المشخص مع العمر والجنس ونمط السكن والمستوى التعليمي. سجلت الدراسة وجود الداء السكري غير المشخص عند 3.1% وما نسبته 10.7% فرط سكر الدم متعلق بالشدة. وبالنتيجة: فان السكر غير المشخص يزداد مع العمر وعند الإناث. This study was conducted to determine the prevalence of undiagnosed mellitus diabetes among adult outpatients at Al-Assad University Hospital. It included 345 patients (189 males (54%), 156 females (46%)). Patients aged 20-90 years were admitted to Al-Assad University Hospital between 2007 and 2008,. They had glucose taken from the venous blood. This study reported 3.1 undiagnosed mellitus diabetes and 10.7% hospital-related hyperglycemia. This study also revealed that undiagnosed mellitus diabetes increased with age, especially in women.